Parental recovered acute kidney injury causes prenatal renal dysfunction and fetal growth restriction with sexually dimorphic implications for adult offspring - Hebert, Jessica F.; Funahashi, Yoshio; Emathinger, Jacqueline M.; Nickerson, Megan N.; Groat, Tahnee; Andeen, Nicole K.; Gurley, Susan B.; Hutchens, Michael P. (Frontiers in Physiology, 2024)
Acute kidney injury (AKI) is rapidly increasing in global incidence and healthcare burden. Prior maternal AKI diagnosis correlates with later pregnancy complications. As pregnancy influences developmental programming, we hypothesized that recovered parental AKI results in poor pregnancy outcomes, impaired fetal growth, and adult offspring disease. Using a well-characterized model of rhabdomyolysis-induced acute kidney injury (RIAKI), a form of AKI commonly observed in young people, we assessed injury 24 hours and 2 weeks after intramuscular glycerol injection by measuring glomerular filtration rate (GFR). AKI impaired renal function but was resolved within two weeks. We bred sham and recovered RIAKI sires and dams in timed, matched matings for gestational day (GD) 16.5 and offspring (birth-12 weeks, 6 months) study. Despite normal GFR pre-pregnancy, recovered RIAKI dams at GD16.5 had impaired renal function, resulting in reduced fetoplacental ratios and offspring survival. Pregnant RIAKI dams also had albuminuria, less renal megalin, and more angiotensin II (AngII) in the proximal tubule brush border than shams, with renal subcapsular fibrosis and higher diastolic blood pressure. Growth-restricted offspring had reduced GFR as older adults with evidence of metabolic inefficiency in male offspring; this correlated with reduced renal AngII levels in female offspring from recovered RIAKI pairings. However, the blood pressures of 6month-old offspring were unaffected by parental RIAKI. Our mouse model demonstrates a causal relationship among RIAKI, gestational risk, and developmental programming of adult-onset offspring GFR and metabolic dysregulation despite parental recovery.